The Effect of Super fine Materials on Some Properties of Hot Mix Asphalt Concrete - N. Abed, Adil; O. Eyada, Sadoon (Iraqi Journal of Civil Engineering, 2012)
The super fine materials constitute that portion of mineral filler finer than 10 microns. The effectiveness of these materials comes from their relation with asphalt film thickness. Asphalt cement grade (40-50) has been used. Nibaay course aggregate and Thmail fine aggregate were combined to achieve the aggregate gradation confirms with the Iraqi Standard Specifications for dense graded mix. Six different types of filler from five locally different sources in Iraq had used and subjected to grain size distribution, specific gravity and chemical composition tests. To study the effect of super fine materials on the performance of HMA mixture, Marshall stiffness, Indirect tensile strength, Moisture susceptibility and Creep tests have been made. Statistical analysis for results has been made. The conclusions referred to the importance of super fine materials due to their effect on HMA concrete properties.